The Effectiveness of Gymbastech Learning Media on The Results of Basic Gymnastics Skills - Fegie Rizkia Mulyana; Agus Arief Rahmat (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
Based on research that was carried out in the previous year regarding the development of Android application-based GYMBASTECH (Gymnastics Basic Techniques) learning media, this study aims to test the effectiveness of GYMBASTECH learning media in the learning process of gymnastics on the results of basic gymnastic skills. This study uses the True Experimental Design research method, while this study uses a posttest-only control design. The population in this study were students majoring in physical education class of 2022. The sampling technique in this study used simple random sampling. The control class consisted of 44 people using conventional learning, and the experimental class consisted of 44 people using the GYMBASTECH learning media. The data collection technique is by conducting a basic exercise skill test according to the assessment rubric in the semester learning plan (RPS). The data analysis technique in this study was the Mann-Whitney test using the SPSS 23.0 program. The results of this study indicate the value of Asymps. Sig. (2-tailed) of 0.032 is smaller than the probability value of 0.05. So thus it can be concluded that the GYMBASTECH learning media is effective for the results of basic gymnastic skills.